1989
DOI: 10.1002/cjce.5450670106
|View full text |Cite
|
Sign up to set email alerts
|

Gas absorption rates in a stirred cell with plane interface in the presence of fine particles

Abstract: The rates of absorption of carbon dioxide into water and into 0.5 mol/L equimolar carbonate buffer solutions (containing varying amounts of arsenite) were measured in a stirred cell with plane interface in the presence of fine solids (activated carbon, kieselguhr and alumina). Experiments show that the absorption rate increases significantly when the activated carbon loading increases up to about 0.2 g/L and thereafter remains constant. No significant effects were observed for other solids. The results could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
4
12
2
Order By: Relevance
“…There it is assumed that the activated carbon or kieselguhr does not affect the reaction rate between C02 and the buffer solution, as discussed by Quicker (1983) and Quicker et al (1986a). Thus k , remains unaffected by solids addition but it can be varied by changing the arsenite concentration.…”
Section: (5)mentioning
confidence: 97%
See 1 more Smart Citation
“…There it is assumed that the activated carbon or kieselguhr does not affect the reaction rate between C02 and the buffer solution, as discussed by Quicker (1983) and Quicker et al (1986a). Thus k , remains unaffected by solids addition but it can be varied by changing the arsenite concentration.…”
Section: (5)mentioning
confidence: 97%
“…The reaction rate constant k , was calculated from the measured NaAsO, concentration and from the estimated ionization to AsO,-. Details of these calculations can be found elsewhere (Quicker et al, 1986a). When the Danckwerts model is used, the gas absorption rate per unit gas-liquid interfacial area, R , is given as:…”
Section: Modeling Of the Bubble Columnmentioning
confidence: 99%
“…This suggests that the insoluble particles and microorganisms are primary responsible for the decrease in the NO absorption rates and that the composition/properties of the liquid phase is of less importance. Negative effects on mass transfer rates by inert particles have been reported in the literature [11][12][13][14]. A possible explanation is the adherence of the particles to the gas-liquid interface, which lowers the effective gas-liquid interfacial area available for gas absorption (vide infra).…”
Section: Experiments With Samplementioning
confidence: 98%
“…These may affect the mass transfer of gasphase component to the liquid phase in various ways. Reductions in mass transfer rates have been reported due to a reduction of the gas-liquid interfacial area, a result of the presence of the suspended solids which (partially) adhere to the gas-liquid interface [12,13]. However, enhancement of mass transfer rates is also possible.…”
Section: Experiments With Biodenox Samples 2 Andmentioning
confidence: 99%
“…Numerous studies relative to the effect of adsorbent particles in three phase absorption (Kars et al, 1979;Alper et al, 1980Alper et al, , 1981Alper et al, , 1986Quicker et al, 1989;Tinge andDrinkenburg, 1992, 1995;Kim and Pingel, 1989) showed that the addition of fine activated carbon particles enhance substantially the liquid side mass transfer coefficient k L whereas larger size particles have no significant or much less effect.…”
Section: Introductionmentioning
confidence: 99%